Accounting expertise and money laundering in Savings and Credit Cooperatives of Peru - Gómez Méndez, Julio (2019)
Objective: Develop an empirical investigation on accounting expertise and money laundering in Savings and Credit Cooperatives of Peru. Method: The research was descriptive because it used bibliographic references to develop the introduction. The research design was non-experimental, since the independent variable was not manipulated to see its effect on the dependent variable, only the phenomenon of asset laundering was observed within the Cooperatives, as presented in its natural context. To meet the objective, surveys have been carried out on Savings and Credit Cooperatives of Peru that are active Results: The respondents state that 60.12% of the Savings and Credit Cooperatives of Peru have not implemented the money laundering and terrorist financing prevention system. Conclusions: The results serve as the basis for new studies linked to the subject of accounting expertise and money laundering, also it searches the implementation of the system of prevention of money laundering and terrorist financing.